Can technology acceptance model be applied on the rural setting: the case of village development and security committee in Malaysia - Abu Samah, Bahaman; Mohamed Shaffril, Hayrol Azril; Abu Hassan, Musa; Alby, Jeffrey Lawrence D'Silva (Science Publications, 2011)
Problem statement: Malaysia has come out with a number of strategies such as National Information Technology Center, Universal Services Provider, Rural Internet Center and Rural Info Center to strengthen and encourage ICT usage among the rural community. Besides the efforts that are brought by the government, do the rural community especially their leaders which are the Village Development and Security Committee use ICT? Approach: The main objective of this study was to investigate any relationship that might occur between variables of Technology Acceptance Model and ICT usage among Village Development and Security Committee. A total of 240 Village Development and Security Committees were selected as the respondents for this study where a developed questionnaire was used to gain the data needed. For the purpose of analysis, SPSS was used where descriptive and inferential analyses were performed. Results: Based on the analyses run, it can be concluded that Village Development and Security Committee in Malaysia have a moderate level of ICT usage. Further analyses run showed that all of the three variables of Technology Acceptance Model namely attitude, perceive ease of use and perceive usefulness have a positive and significant relationship with ICT usage while attitude was detected as the main contributor towards ICT usage among Village Development and Security Committee. Conclusion/Recommendation: This study has revealed that Technology Acceptance Model that was used to explain ICT usage can be applied within the Malaysian rural setting. It also can be concluded that Village Development and Security Committee with a high level of attitude, perceive ease of use and perceive usefulness towards ICT will have higher level of ICT usage. To further develop and sustain this high level of attitude, perceive ease of use and perceive usefulness towards ICT usage, Village Development and Security Committee must be frequently exposed to ICT information and knowledge. It is recommended that ICT house to house training can be conducted among the Village Development and Security Committee by the related agencies.